CS-5 A case of anaplastic pleomorphic xanthoastrocytoma in the pineal region. (6th December 2021) - Nakayama, Noriyuki; Yamada, Ryuta; Yamada, Tetsuya; Iwama, Toru
Abstract: Tumors in the pineal gland are rare tumors that account for about 0.3% of all brain tumors and have various histological types of tumors develop with germinoma, pineocytoma, and pineoblastoma in that order. On the other hand, pleomorphic xanthoastrocytoma (PXA) is a rare tumor of less than 0.2% and frequently occurs in supratentorial cerebral surface of children and young adults.A case was a 61-year-old man whose pineal tumor was found due to visual disturbance. MRI showed a 23 mm-sized lesion with cysts and inhomogeneous enhancement in the pineal gland. Partial calcification was observed, but there was no non-communicating hydrocephalus, and no increase in HCG-β and AFP with blood sampling. A midline suboccipital craniotomy was performed in the sitting position, a head-up surgery was performed using a 4K / 3D video microscope system (ORBEYE exoscope, Olympus) by the infratentorial supracerebellar approach (ITSCA). The bridging veins and precentral cerebellar vein were dissected to expose the posterior surface of the tumor, and internal decompression was performed. For the complication of air embolism, artificial cerebrospinal fluid was sprayed, and the bilateral internal jugular veins were compressed to confirm the inflow point. There was strong adhesion to the Rt vein of Rosenthal, and the site was removed intracapsularly. Finally, subtotal resection was performed with remaining the upper part of the tumor, a blind lesion behind the Vein of Galen. Vertical gaze palsy occurred after this operation, but it gradually improved over time. Tumor showed pathologically remarkable polymorphism, poor microvascular proliferation and necrosis, but mitotic figures 4–5 / 10HPF, MIB-1 index 10%, GFAP positive, no BRAF V600E mutation. There are few reports of PXA occurring in the pineal gland, and this case is the sixth case. It is also the first report for pineal tumors using ORBEYE through ITSCA in the sitting position.